Psychological Empowerment, Its Effect On Employee Creativity Through Intrinsic Motivation - Ari Prasetyo Hirmawan; Pardiman Pardiman; Muhammad Reza Aswinaryanto; Muhammad Agus Supriyanto (IQTISHODUNA, 2023)
Empowerment is the main key to the motivation and productivity of an employee so that they can give maximum contribution to the company. Employee engagement and empowerment direct them to help each other both for themselves, between employees and for the company. The involvement and empowerment of employees are very effective in maintaining high levels of employee motivation. This study aims to determine the effect of psychological empowerment on employee creativity through intrinsic motivation. This study used a quantitative explanatory research approach. This study proposes several hypotheses with a total sample of 105 respondents. Data in this study were collected using a research instrument in the form of a questionnaire and analyzed using the PLS (Partial Least Square) analysis test. The results of this study indicate that psychological empowerment does not directly affect employee creativity. However, psychological empowerment significantly affects employee creativity through intrinsic motivation, and intrinsic motivation mediates the full/perfect mediation effect of psychological empowerment on employee creativity